An Integrated 3D Hydrophilicity/Hydrophobicity Design for Artificial Sweating Skin (i‐TRANS) Mimicking Human Body Perspiration - Peng, Yucan; Zhou, Jiawei; Yang, Yufei; Lai, Jian‐Cheng; Ye, Yusheng; Cui, Yi (Advanced materials (Weinheim), 2022)
Artificial skins reproducing properties of human skin are emerging and significant for study in various areas, such as robotics, medicine, and textiles. Perspiration, as one of the most imperative thermoregulation functions of human skin, is gaining increasing attention, but how to realize ideal artificial skin for perspiration simulation remains challenging. Here, an integrated 3D hydrophilicity/hydrophobicity design is proposed for artificial sweating skin (i‐TRANS). Based on normal fibrous wicking materials, the selective surface modification with gradient of poly(dimethylsiloxane) (PDMS) creates hydrophilicity/hydrophobicity contrast in both lateral and vertical directions. With the additional help of bottom hydrophilic Nylon 6 nanofibers, the constructed i‐TRANS is able to transport “sweat” directionally without trapping undesired excess water and attain uniform “secretion” of sweat droplets on the top surface, decently mimicking human skin perspiration situation. This fairly comparable simulation not only presents new insights for replicating skin properties, but also provides proper in vitro testing platforms for perspiration‐relevant research, greatly avoiding unwanted interference from the “skin” layer. In addition, the facile, fast, and cost‐effective fabrication approach and versatile usage of i‐TRANS can further facilitate its application. A facile surface modification method for fibrous materials is developed to fabricate artificial sweating skin, based on an integrated 3D hydrophilicity/hydrophobicity design. With the hydrophilicity/hydrophobicity contrast in both the lateral and vertical directions, the constructed “skin” can transport “sweat” directionally without trapping undesired excess water and attain uniform “secretion” of sweat droplets on the top, decently mimicking human skin perspiration situation.